Effects of extracorporeal photopheresis on survival in chronic graft versus host disease - Kaya, Ahmet; Kaya, Emin; Kuku, Irfan; Erkurt, Mehmet Ali; Berber, Ilhami; Bicim, Soykan; Uysal, Ayse (Marmara Univ, Fac Medicine, 2024)
Objective: Chronic graft versus host disease (cGVHD) develops after allogeneic hematopoietic cell transplantation, when immune cells from a non-identical donor initiate an immune reaction against the transplant recipient. Extracorporeal photopheresis (ECP) can be used in combination with prednisone in steroid-resistant cGVHD. In this study, the effect of ECP use on survival in cGVHD was examined. Patients and Methods: Twenty-six patients who were followed up in the adult Hematology Clinic of Inonu University Turgut Ozal Medical Center for cGVHD were included in the study. Stem cell transplantation and ECP application parameters that may affect the survival of the patients were examined. Results: The degree of involvement in cGVHD affects survival. Involvements with clinical and laboratory scores of 2 and above according to the National Institutes of Health consensus criteria, significantly reduced survival. The development time of cGVHD was found to be associated with survival, and that it had a positive impact on survival, especially when the disease developed after 220 days after the transplantation. It was observed that steroid dose taken during ECP, patient age and cGVHD prophylaxis used affected survival. Conclusion: The use of ECP may be effective in survival, especially, in patients who develop cGVHD, 220 days after allogeneic transplantation. Concurrent use of steroids with ECP affects survival.
Keywords: Graft versus host disease; Allogeneic hematopoietic cell transplantation; Extracorporeal photopheresis; Survival